Lupus erythematosus panniculitis: A case report - Besma Ben Dhaou; Asma kefi; Zohra Aydi; Imen Rachdi; Houda Hammami; Fatma Daoud; Ehsen Ben Brahim; Sami Fenniche; Achraf Debbiche; Fatma Boussema (Journal of Dermatology and Dermatologic Surgery, 2017)
Lupus erythematosus panniculitis (LEP), an uncommon variant in the clinicopathological spectrum of lupus erythematosus (LE), is rare. There are only a few reported series of patients with this condition; none in individuals of North African ancestry. LEP is characterized by inflammation of the deep dermis and subcutaneous tissue. It usually consists of nodules and hardened subcutaneous plaques on the forehead, cheeks, proximal extremities, and buttocks. Leg involvement is rare and can lead to misdiagnosis. A case of LEP, with unusual involvement of legs, is reported in a 40-year-old woman who had the diagnosis of systemic lupus erythematosus (SLE) four years ago.